Isolasi dan Identifikasi Bakteri Salmonella sp. pada Ayam Broiler - Loe, Fhady Risckhy; Putra Nugroho, Mega Perkasa; Tangkonda, Elisabet; Gelolodo, Maria Aega; Sanam, Maxs Urias Ebenhaizar (Jurnal Veteriner dan Biomedis, 2025)
Salmonella sp. is one of the dangerous pathogens that causes salmonellosis in humans and animals. Salmonella sp. bacteria. usually inhabit the intestines of most animal species, but are also found in the environment. Salmonella sp. can survive for long periods of time, allowing bacteria to move from one place to another through equipment, including contaminated feed. This case report aims to determine the technique and interpretation of the results of each laboratory test in identifying Salmonella sp. Which is obtained through swabbing the chicken's cloaca. The testing stages include sampling, laboratory testing, and identification of test results. Sampling was carried out at the Naikoten I Inpres Market, Kupang City and laboratory testing was carried out at the Bacteriology Laboratory of the Veterinary Medicine Study Program, Nusa Cendana University. The isolation results found Salmonella sp. SSA media is black, because Salmonella produces hydrogen sulfide (H2S). The results of gram staining showed that the bacteria were in the form of cocobacillus and were gram negative. Biochemical testing of Salmonella sp. is negative in the Indol test, produces H2S, is non-motile, and catalase positive.